Skewed sex ratios and violence against women in Pakistan - Olympia L. K. Campbell; Maheen Pracha; Ruth Mace (Evolutionary Human Sciences, 2025)
Concerns have been raised that an excess of men leads to societal violence, including violence against women, although recent evidence has challenged this view. One area that remains untested is honour killings, a type of femicide perpetrated by unrelated family members, such as intimate partners, and related family members, such as parents and siblings. Using a novel data set of media reports of honour killings from Pakistan we test whether the sex ratio is associated with femicide. To address reporting bias, we implement two case-control studies. The first compares media reports of honour killings to male suicides. The second compares honour killings perpetrated by unrelated individuals to those perpetrated by kin. We find evidence that honour killings perpetrated by unrelated individuals are higher in male-biased areas compared to those perpetrated by kin. Honour killings of women by kin therefore appear less sensitive to the sex ratio. Results align with sexual selection theory, suggesting more male competition may lead to more violence. We also find weak evidence that male-biased areas report more male suicides than honour killings. However, we caution against drawing causal conclusions due to potential confounding variables, particularly economic deprivation. This highlights the challenges of studying sensitive topics quantitatively.